Long‐term analysis of adalimumab in Japanese patients with moderate to severe hidradenitis suppurativa: Open‐label phase 3 results. Issue 1 (7th October 2020) - Morita, Akimichi; Takahashi, Hidetoshi; Ozawa, Kentaro; Imafuku, Shinichi; Takekuni, Nakama; Takahashi, Kenzo; Matsuyama, Takashi; Okubo, Yukari; Zhao, Yiwei; Kitamura, Susumu; Takei, Keiko; Yokoyama, Masayuki; et al.
Abstract: This phase 3, multicenter, open‐label single‐arm study evaluated adalimumab (ADA) in Japanese patients with moderate to severe hidradenitis suppurativa (HS). Fifteen patients received ADA 160 mg s.c. at week 0, 80 mg at week 2 and 40 mg at week 4 and every week thereafter. At any time after week 52, patients were given the option to receive 80 mg ADA every other week or remain on 40 mg every week. The primary end‐point (achievement of HS Clinical Response [HiSCR] at week 24) and results up to week 24 were published previously. Secondary end‐points included total abscess and inflammatory nodule (AN) count, 30% or more and 1 unit or more reduction in Patient's Global Assessment of Skin Pain Numeric Rating Scale (NRS30), modified Sartorius score and quality of life (QoL). After 12 weeks of ADA treatment, the achievement rate in HiSCR was 86.7%; HiSCR achievement rate was sustained through week 52 at 66.7%. Improvements at week 12 were also seen in the proportion of patients achieving an AN count of 0–2; NRS30 response rate among the nine patients with a baseline NRS of 3 or more; mean decrease in modified Sartorius score (61.4); and QoL as assessed by Dermatology Life Quality Index and Treatment Satisfaction Questionnaire; these improvements were maintained through 52 weeks. Similar efficacy was observed when patients switched dosing from ADA 40 mg every week to ADA 80 mg every other week. There were no new safety findings with ADA 40 mg weekly dosing during the study, and no differences in safety were found between patients who switched to 80 mg ADA every other week and patients who remained on 40 mg every week. The results of this study indicate that long‐term ADA treatment is effective and well tolerated in Japanese patients with moderate to severe HS.